歯学部５年生に対する口腔・咽頭領域の医療行為（医業）に関するアンケート調査 - Sato Takashi (Stomato-pharyngology, 2008)
The treatment areas covered within the specialty of dentistry and oral surgery are generally defined as “places affecting the lips, buccal mucosa, superior and inferior alveoli, hard palate, anterior 2/3 of tongue, floor of mouth, soft palate, jaw bone (including mandibular joint), and salivary glands (excluding parotid gland).”However, the regulations for these dentistry and oral surgery treatment areas have no legally binding authority, and so the fact is that today dentistry and oral surgery departments and clinics overtly conduct medical practice in the neck and head regions.We conducted a questionnaire survey of 120 fifth-year students in the Aichi Gakuin University School of Dentistry on medical practices in the oral and pharyngeal regions.The questionnaire was focused on the following four items:1. The area of medical care covered by the specialty of dentistry and oral surgery2. Is the palatine tonsil an area to be treated in dentistry and oral surgery?3. The treatment of dysphagia (aspiration)4. The treatment of obstructive sleep apnea syndrome (OSAS)The following results were obtained:1. The currently defined range of medical care in the specialty of dentistry and oral surgery was considered to be “an appropriate range” by 69.2% of respondents, and “too narrow” by 23.3% of students.2. With regard to the palatine tonsil, 50.0% were of the opinion that “it should be treated in some cases, ” and 25.8% that it is “subject to treatment” in the field.3. With regard to the treatment of dysphagia, 57.5% thought that “involvement should be focused on oral care, ” and 37.5% that “involvement should be by the team leader.”4. In the treatment of OSAS, 82.5% thought that “they should be involved in mild cases in which oral appliances are effective.”These results are reported with some consideration of the literature. 標榜診療科としての歯科口腔外科の診療領域の対象としては, 原則として「口唇, 頬粘膜, 上下歯槽, 硬口蓋, 舌前2/3, 口腔底に, 軟口蓋, 顎骨 (顎関節を含む), 唾液腺 (耳下腺を除く) を加える部位とする」と規定されている. 我々は, 歯学部学生に対して, これら歯科口腔外科の診療範囲を充分に踏まえて, 耳鼻咽喉科の講義を担当している. この歯科口腔外科の診療領域に対する規定は法的な拘束力を持たないため, 歯科口腔外科による頭頚部領域における医療行為 (医業) が公然と行われているのも事実である. 今回我々は, 愛知学院大学歯学部5年生120名に対して, 口腔・咽頭領域の医療行為 (医業) に関するアンケート調査を実施した.